Differentiation of Bone Mesenchymal Stem Cells Into Vascular Endothelial Cell-Like Cells Using Functionalized Single-Walled Carbon Nanotubes - Luo, Feng; Li, Ruyi; Zheng, Huaping; Xu, Yichen; Yang, Linxin; Qu, Changxing; Hong, Guang; Wan, Qianbing (Frontiers in Bioengineering and Biotechnology, 2022)
Carbon nanotubes (CNTs) are a promising bioactive scaffold for bone regeneration because of their superior mechanical and biological properties. Vascularization is crucial in bone tissue engineering, and insufficient vascularization is a long-standing problem in tissue-engineered scaffolds. However, the effect of CNTs on vascularization is still minimal. In the current study, pristine single-walled carbon nanotubes (SWNTs) were purified to prepare different ratios of SWNTs/EDC composites, and their surface morphology and physicochemical properties of SWNTs/EDC were studied. Furthermore, the effect of SWNTs/EDC on vascularization was investigated by inducing the differentiation of bone mesenchymal stem cells (BMSCs) into vascular endothelial cell-like cells (VEC-like cells). Results showed that SWNTs/EDC composite was successfully prepared, and EDC was embedded in the SWNTs matrix and uniformly distributed throughout the composites. The AFM, FTIR spectra, and Raman results confirmed the formation of SWNTs/EDC composites. Besides, the surface topography of the SWNTs/EDC composites presents a rough surface, which may positively affect cell function. In vitro cell culture revealed that SWNTs and SWNTs/EDC composites exhibited excellent biocompatibility and bioactivity. The SWNTs/EDC composite at mass/volume ratios 1:10 had the best enhancement of proliferation and differentiation of BMSCs. Moreover, after culture with SWNTs/EDC composite, approximately 78.3% ± 4.2% of cultured cells are double-positive for FITC-UEA-1 and DiI-Ac-LDL double staining. Additionally, the RNA expression of representative endothelial cell markers VEGF, VEGF-R2, CD31, and vWF in the SWNTs/EDC composite group was significantly higher than those in the control and SWNTs group. With the limitation of our study, the results suggested that SWNTs/EDC composite can promote BMSCs differentiation into VEC-like cells and positively affect angiogenesis and bone regeneration.